Trehalose Recycling Promotes Energy-Efficient Biosynthesis of the Mycobacterial Cell Envelope - Amol Arunrao Pohane (American Society for Microbiology, 2021)
The mycomembrane layer of the mycobacterial cell envelope is a barrier to environmental, immune, and antibiotic insults. There is considerable evidence of mycomembrane plasticity during infection and in response to host-mimicking stresses.